If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10y+5=6y+41
We move all terms to the left:
10y+5-(6y+41)=0
We get rid of parentheses
10y-6y-41+5=0
We add all the numbers together, and all the variables
4y-36=0
We move all terms containing y to the left, all other terms to the right
4y=36
y=36/4
y=9
| 13=3v+1 | | 3x+44=125 | | 6−0.8(g−10)=0.3(4g−10) | | 15=u+2u | | (x-12)^12=-27 | | 11=1=3q | | 5x-6=+9 | | 2x+29=60 | | -11=1=3q | | n=7+(32÷16)×4-6 | | 16/3x=4/9 | | h÷2+h÷5=14 | | x16/3=4/9 | | 50=10(z−91) | | 63.4=-9.8x^2+45x+1 | | 2x+x+42=90 | | 6-5(4d-3)=7(3-4d)+8 | | .2t^2=t+.5 | | h+3/7=1 | | g3+ 16= 24 | | 8=5a+3 | | 2-22=2x-1 | | 87=x-(.05*x) | | K×x^2-4x-5=0 | | 3^5x-8=9^x-2 | | -5(2x+1=25 | | 3^5x-8=9x-2 | | 6-5=13-3x | | 1=4w=9 | | 6x+2(2x-1)+3=10 | | -1.3=11.5+v/8 | | (u-11)=5 |